Cardiac angiosarcoma: A diagnostic and therapeutic challenge. Issue 2 (August 2020) - Krishnan, Tharani; Pettersson, Gosta; Mukherjee, Rahul; Singhal, Nimit
Abstract: Cardiac angiosarcomas are a rare group of soft tissue sarcomas, characterized by aggressive local growth and early spread. Because this is an uncommon disease, there is currently no standard treatment approach. When localized, surgery appears to lead to the best outcomes, but this can be technically challenging and not always feasible. Upfront chemoradiotherapy provides an alternative that may shrink the tumor to enable definitive surgical resection. We report a case of primary cardiac angiosarcoma with a complete metabolic and pathological response after upfront chemoradiotherapy with paclitaxel, who then underwent surgery, as a potential treatment option for patients with this rare condition. <Learning objective: Cardiac angiosarcoma can present with non-specific symptoms and signs making early diagnosis difficult. When localized, surgery provides the best survival outcomes for patients, but may not be possible due to the extent of invasion into surrounding critical structures. In this case of locally advanced disease in a young patient, there was the opportunity to treat this tumor aggressively with upfront combined chemoradiotherapy followed by surgery, with a dramatic response observed.>